Comparison of Clinical Assessment and Adhesive-Tape Laboratory Microscopic of Sarcoptes scabiei for Scabies Diagnostic - Rifqoh Rifqoh; Wahdah Norsiah; Neni Oktiyani (Medical Laboratory Technology Journal, 2021)
Scabies infestation caused by Sarcoptes scabiei mite that infected the skin by making the tunnel burrow. Diagnosis of scabies infestation commonly relies on clinical assessment (CA). However, some scabies symptoms are similar to other diseases. Diagnosis of confirmed scabies can be made by identifying egg or Sarcoptes scabiei mite or scybala through skin scraping laboratory microscopic examination, which was the adhesive tape microscopic (AT) a noninvasive alternative. We aimed to compare the scabies diagnostic accuracy of CA and AT in Islamic Boarding School. This study was an analytical observational cross-sectional study. The population was 94 students of Islamic Boarding School, determining the sample base on purposive sampling technique. There were 34 samples with presumptive scabies analyzed with CA by two clinicians and AT by two trained laboratory technicians. The result showed that the number of patients who positive scabies by CA was 14 (41.18 percent) and 31 (91.18 percent) by AT. Sensitivity was 41.93 percent for CA and 92.85 percent for AT, and the difference was significantly based on Cohen's kappa (ⱪ=0.024). The number of positive cases with both techniques was 13 (38.24 percent). The number of patients positive with only CA was 1 (2.93 percent), and only AT was 18 (22.9 percent). The accuracy of CA was only 44,11 percent. The study concluded that CA is low accuracy than AT. The adhesive tape test is easy, needs no expensive equipment. It is recommended that adhesive tape test for screening purposes. The appropriate comprehensive of both methods for scabies diagnostic is highly recommended.